Seismic Risk - World Bank (Washington, DC: World Bank, 2021)
The importance of ensuring that dam structures can withstand earthquakes has been recognized and practiced for many years. The technical capability of the dam engineering industry in the seismic design of dam structures has increased considerably since the 1980-1990s. Dams designed using modern seismic engineering principles that are well constructed have performed well during earthquakes, with only modest damage. Older dams that have suffered damage from earthquakes are likely to have been subjected to poor construction or maintenance, or they lack modern defensive design measures to prevent failure. Seismic hazard varies around the world. Some countries experience major earthquakes frequently, whereas other countries have hardly ever experienced one. This technical note contains the minimum level of technical detail for seismic design of new structures and seismic assessment of existing structures, so that non-specialists can use it. The key objective is to provide guidance for addressing seismic aspects of dam projects early on in project preparation. The note is intended to raise awareness and inform specific studies and investigations, as appropriate, during project preparation. The material presented should be used to assess the required level of seismic hazard assessment, review the adequacy of the dam’s seismic design and resilience measures, and recommend required expertise for quality assurance of projects involving dams in seismic areas.